2017
DOI: 10.1016/j.jcm.2016.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Manual Therapy Combined With Physical Therapy in Treatment of Patellofemoral Pain Syndrome: Systematic Review

Abstract: Objectives: The purpose of this study was to conduct a review of randomized controlled trials (RCTs) to determine the treatment effectiveness of the combination of manual therapy (MT) with other physical therapy techniques. Methods: Systematic searches of scientific literature were undertaken on PubMed and the Cochrane Library (2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014). The following terms were used: "patellofemoral pain syndrome," "physical therapy," "manual therapy," and "manipulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 37 publications
1
20
0
6
Order By: Relevance
“…Figure 1 summarises the updated consensus process. We identified two low-quality systematic reviews15 16 and three moderate-quality RCTs17–19 on exercise therapy; one low-quality systematic review20 and one moderate-quality RCT21 on combined interventions; one high-quality22 and two low-quality23 24 systematic reviews and two RCTs (one high-quality,25 one low-quality26) on patellar taping and bracing; and two high-quality,27 28 three moderate-quality18 29 30 and two low-quality31 32 RCTs on other adjunctive interventions. No new systematic reviews or RCTs were identified that related to foot orthoses.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1 summarises the updated consensus process. We identified two low-quality systematic reviews15 16 and three moderate-quality RCTs17–19 on exercise therapy; one low-quality systematic review20 and one moderate-quality RCT21 on combined interventions; one high-quality22 and two low-quality23 24 systematic reviews and two RCTs (one high-quality,25 one low-quality26) on patellar taping and bracing; and two high-quality,27 28 three moderate-quality18 29 30 and two low-quality31 32 RCTs on other adjunctive interventions. No new systematic reviews or RCTs were identified that related to foot orthoses.…”
Section: Resultsmentioning
confidence: 99%
“…The Jadad scale ranges from 0–5. If the Jadad score was ≥3 points, the trial was considered high‐quality research, whereas if the Jadad score was ≤2 points, the study was considered a low‐quality trial (Espí‐López, Arnal‐Gómez, Balasch‐Bernat, & Inglés, ; Jadad et al, ; Seminario‐Amez, López‐López, Estrugo‐Devesa, Ayuso‐Montero, & Jané‐Salas, ; Zhang, Lan, Pen, & Li, ).…”
Section: The Reviewmentioning
confidence: 99%
“…Numerous treatment strategies have been developed for chronic pain, including medications,19 massage,20 acupuncture,21 stretching,22 physical medicine,23 cognitive-behavioral therapy,24 and alternative therapies 25. In these treatments, especially, the mechanical stimulation (eg, thermal stimulation, pinch, or electrostimulation), which is contained in either the physical medicine or the alternative therapies, has already been reported to have an inhibitory effect on pain 2628.…”
Section: Introductionmentioning
confidence: 99%